Functional Ultrasound Imaging of Spinal Cord Hemodynamic Responses to Epidural Electrical Stimulation: A Feasibility Study - Song, Pengfei; Cuellar, Carlos A.; Tang, Shanshan; Islam, Riazul; Wen, Hai; Huang, Chengwu; Manduca, Armando; Trzasko, Joshua D.; Knudsen, Bruce E.; Lee, Kendall H.; Chen, Shigao; Lavrov, Igor A. (Frontiers in Neurology, 2019)
This study presents the first implementation of functional ultrasound (fUS) imaging on the spinal cord to monitor its hemodynamic responses to epidural electrical spinal cord stimulation (SCS) on two animal models. SCS has been successfully applied to control chronic refractory pain and recently was evolved to alleviate motor impairment in Parkinson’s disease and spinal cord injury. At present, however, the mechanisms underlying SCS are mainly unclear, and current methods for monitoring SCS are limited in their capacity to provide the required sensitivity and spatiotemporal resolutions to evaluate local responses to SCS. fUS is an emerging technology that has recently shown promising results in monitoring a variety of neural activities associated with the brain. Here we demonstrated the feasibility of performing fUS on two animal models during SCS. We showed in vivo spinal cord hemodynamic responses measured by fUS evoked by varied SCS parameters. We also demonstrated that fUS has higher sensitivity in monitoring spinal cord response than electromyography. The high spatial and temporal resolutions of fUS were demonstrated by localized measurements of hemodynamic responses at different spinal cord segments, and by reliable tracking of spinal cord responses to patterned electrical stimulations, respectively. Finally, we proposed optimized fUS imaging and post-processing methods for spinal cord. These results support feasibility of fUS imaging of the spinal cord and could pave the way for future systematic studies to investigate mechanisms of spinal cord neuromodulation in vivo.